Exploring learning experiences for UiTM Perlis accounting students through Accounting Global Week / Nor Kartini Mohd Rodzi ... [et al.] - Mohd Rodzi, Nor Kartini; Naiimi, Nazirah; Abdul Rahman, Norshimah; Mohd Noor, Marjan; Abdullah, Azrul (Universiti Teknologi MARA, Perlis, 2024)
Global learning experience creates opportunities for students to engage and attain international and professional competencies. To enhance learning experience in global learning session, a high impact Accounting Global Week (AGW) program was conducted on 128 accounting students at UiTM Perlis. The program involves collaborative events with the institution members within Malaysia and abroad, in which experts, academia can join and participate in sharing of experiences, skills and knowledge on the current issues and challenges in the field of accounting. Inadequate learning experience related to accounting subject has resulted from poor engagement exposure and weak thinking skills which are needed for success. This study aims to explore learning experiences for UiTM Perlis accounting students through AGW. Exploratory research design was employed in this study through observations and review of feedback form. The result of the learning experience included online global learning sessions conducted via video conference, active student engagement and positive responses from participants. The global learning session has proven to be helpful for students in enhancing their knowledge and engaging with international educators. It is recommended to extend this study to different courses and for a longer period.